Determinants of demand for private long-term care insurance (empirical evidence from Poland) - Łukasz Jurek; Wioletta Wolańska (Risks, 2021)
The main aim of the article is to evaluate determinants of demand for private long-term care insurance in Poland. Since this type of insurance is not (yet) offered on the market, the demand was examined through a survey in which respondents declared their willingness to purchase it. From the obtained results, it can be concluded that Poles declare a high propensity for private protection in the event of dependence. The vast majority (almost two-thirds) of the respondents were interested in purchasing long-term care insurance, while only one in sixteen respondents showed no such interest. Factors that predominantly determine the willingness to buy are as follows: individual foresight, knowledge about the costs of long-term care, preferences regarding methods of financing care, having children, and the level of education.
Keywords: 330; dependency; long-term care; private insurance